Pengaruh Komunikasi dan Beban Kerja Terhadap Kinerja Karyawan Pada PT Mitra Tunas Harapan Tahun 2024 - Inayatuddiniyah Inayatuddiniyah; Muyasaroh Muyasaroh; Basuki Rahmat; Pinki Rizki Agustin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee performance is the result of an individual's efforts in carrying out their duties and responsibilities, which is reflected in the quality and quantity of work achieved. PT. Mitra Tunas Harapan, a company engaged in providing construction services in Cilegon, has various activities that include planning, design, project supervision, and construction management services. To achieve company goals, employee performance is one of the important factors influencing the company's operational success. Several factors believed to influence employee performance include communication and workload. This study aims to analyze the effect of communication and workload on employee performance at PT. Mitra Tunas Harapan. This study involved a population consisting of 36 employees at the company. The sampling technique used was nonprobability sampling with a total sampling method, meaning the entire population was sampled in this study. The results showed that communication partially had a positive and significant effect on employee performance. This indicates that good communication between superiors and employees, as well as between employees, can improve task understanding and streamline work processes, which ultimately contribute to improved performance. In addition, workload was also shown to have a positive and significant effect on employee performance. A workload that matches employee capacity can improve their productivity and work quality. Simultaneously, both communication and workload have a positive and significant impact on employee performance. Therefore, companies need to address both factors to improve employee performance and optimally achieve company goals. Furthermore, this study highlights the importance of effective communication management within organizations. Clear and open communication between managers and employees can reduce misunderstandings and improve coordination in carrying out tasks.